Understanding the Oxygen Reduction Reaction Activity and Oxidative Stability of Pt Supported on Nb‐Doped TiO2. Issue 15 (5th March 2019) - He, Cheng; Sankarasubramanian, Shrihari; Matanovic, Ivana; Atanassov, Plamen; Ramani, Vijay
Abstract: Commercial fuel cell electrocatalyst degradation results from carbon electrocatalyst support oxidation at high operating potential transients. Guided by density functional theory (DFT) calculations, Nb‐doped TiO2 (NTO) was synthesized, which exhibits a unique combination of high surface area, high electrical conductivity, and high porosity. This catalyst retained 78 % of its initial electrochemically active surface area compared with 57.6 % retained by Pt/C following the DOE/FCCJ protocol for accelerated stability test. Strong metal–support interactions, which were predicted by DFT calculations and confirmed experimentally by X‐ray photoelectron spectroscopy and kinetics measurements, resulted in 21 % higher oxygen reduction reaction mass activity (at 0.9 V vs. reversible hydrogen electrode) on Pt/NTO compared with commercial Pt/C. The ex situ activity and durability of Pt/NTO translated to a fuel cell. The rise in electrode ohmic resistance and non‐electrode concentration overpotential indicate that improving the conductivity of NTO and optimizing the catalyst ink formulation are critical next steps in the development of Pt/NTO‐catalyzed proton exchange membrane fuel cells. Abstract : Bettering the best : Pt supported on Nb‐doped TiO2 is an excellent fuel cell electrocatalyst that exhibits excellent durability (35 % more stable than the commercial state‐of‐the‐art catalyst) and activity (20 % more active than the commercial state‐of‐the‐art catalyst) after accelerated tests that simulated real‐world use.